Hubungan Intensitas Mengikuti Ekstrakurikuler Pramuka dengan Kecerdasan Moral SiswaKelas VIII di MtsN 9 Hulu Sungai Selatan - Hamidah, Hamidah; Hairina, Yulia; Imadduddin, Imadduddin (Jurnal Al-Husna, 2022)
The purpose of this research is to find out the level and the correlation between intensity following the scout extrakuricular to moral quotient of  student class VIII MTsN 9 Hulu Sungai Selatan. Field research with a quantitative approach. The data collection device uses the likert scale, scale aspect of intensity following the scout extrakuricular 29 aitems and moral quotient scale 23 aitems that have been tested for validity and reliability. The sampling technique used was purposive sampling, with a total of 53 people. The data analysis using SPSS software for Windows 21.0. Quantitative data shows intensity following the scout extrakuricular in the medium category (71,7%) and moral quotient  in the medium category (73,6%).  A correlation analysis results uses a pearson product moment technique in the can calculated r value is 0,588 with p value 0,000 while the r table is at the 5% significance level with N = 53 of 0,270 show off that intensity following the scout extrakuricular affected the level of moral quotient. As for the magnitude of the contribution of intensity following the scout extrakuricular variable to the moral quotient of MTsN 9 Hulu Sungai Selatan in the amount of (rxy2 x 100) or 34,6%.